Requisitos de iluminação natural nos sistemas de avaliação de edificios e impactos energéticos em edificações comerciais no Brasil - Santos, Laila Souza (2012)
In the last decades, many countries started certifying buildings with a supposed superior environmental performance. In Brazil, the use of building assessment systems originally developed in countries with their own construction practices, energy, geography and climate conditions, has generate a lot of criticism in academia. An example would be the exigency, in Brazil, that sustainable buildings were to meet the daylight requirements of assessment systems proposed for sites where the availability of daylight is considerably lower than it is in Brazil and where the demand for heating is real in winter times. This work started from the premise that the application of these systems could encourage the construction of energy-inefficient buildings in Brazil, caused by the introduction of excessive daylight in architectural interiors. Thus, the aims here consisted of evaluating the energy impacts of meeting the daylight requirements set by imported systems with possible application in Brazil, such as AQUA, BREEAM and LEED. The methodological procedures included development of parametric models with different solar orientations, window-to-wall ratio (WWR), shading devices and protection angles. These models were simulated in DIALux and DesignBuilder softwares in five brazilian cities, in order to identify the models meeting the daylight requirements in building assessment systems and to measure their energy impacts when subjected to different brightness of the sky. The results allowed to identify that methodologies based on daylight factor (DF) as an indicator of daylight use does not favor the proposition of more energy-efficient buildings and that, in general, there is little consensus on what is considered appropriate for luminous performance, since only one third of the models meet the requirements in all assessment systems investigated. Among them, all simuntaneously presented WWR of 100% and the use of shading devices, which increase the energy consumption spent with electric lighting and air conditioning by about 20% when compared to similar models with WWR of 50%, indicating that rating systems do not necessarily represent improvements in environmental performance of buildings.